2015
DOI: 10.1098/rsta.2014.0086
|View full text |Cite
|
Sign up to set email alerts
|

Seismic analysis of offshore wind turbines on bottom-fixed support structures

Abstract: This study investigates the seismic response of a horizontal axis wind turbine on two bottom-fixed support structures for transitional water depths (30-60 m), a tripod and a jacket, both resting on pile foundations. Fully coupled, nonlinear time-domain simulations on full system models are carried out under combined wind-wave-earthquake loadings, for different load cases, considering fixed and flexible foundation models. It is shown that earthquake loading may cause a significant increase of stress resultant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 22 publications
3
39
0
Order By: Relevance
“…Alati et al [35] studied the seismic responses of bottom-fixed OWTs under different earthquakes and the soil effect was considered. They found that the resultant demands of tower-base moment and tower-top displacement were significantly increased by the earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Alati et al [35] studied the seismic responses of bottom-fixed OWTs under different earthquakes and the soil effect was considered. They found that the resultant demands of tower-base moment and tower-top displacement were significantly increased by the earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…The critical effect of the earthquake loading on these energy infrastructures has been further corroborated by the detailed research of Alati et al ., who studied the seismic response of an offshore horizontal axis wind turbine assumed with either a tripod or a jacket supporting system. Particularly, a multi‐hazard environment was considered under the combined exposure of wind, wave and earthquake, while the latter was represented by 49 pairs of strong ground motions horizontal components recorded during past seismic events.…”
Section: Seismic Evaluation Of Wind Turbines Based On Numerical Simulmentioning
confidence: 99%
“…Similar conclusion has been drawn elsewhere, while the higher rotor blade modes, captured only by a full system model, were also found important for the seismic response because they may correspond to the region of maxima spectral accelerations. 46,47,75,98 With such a motivation to study an integrated bladetower-foundation model subjected to the seismic loading, Jin et al 99 utilized the MBS approach and an artificial accelerogram (PGA = 0.36 g), which was imposed to perform RHA, induced high fluctuation (over 180%) for the section forces (i.e., bending moments and axial force) mainly at the tower's base. This variation in critical demand measures because of the sudden earthquake occurrence was found to disturb the wind turbine performance in terms of energy harness signifying the adverse seismic implications on wind turbines even in case of no imposed structural damages.…”
Section: Seismic Analysis Of Wind Turbines Within a Deterministic Framentioning
confidence: 99%
“…In the theme issue, the papers by Muskulus [55] and by Alati et al [56] present numerical studies on offshore wind turbines under normal and extreme loading conditions of particular interest.…”
Section: Design Load Casesmentioning
confidence: 99%
“…Alati et al [56] investigate the seismic response of the baseline NREL 5 MW wind turbine [44], mounted on two different bottom-fixed substructures for transitional waters, a tripod and a jacket. The study is carried out by fully coupled nonlinear time-domain simulations on full system models (i.e.…”
Section: Design Load Casesmentioning
confidence: 99%